TEOR DE SÓDIO E OUTROS ÍONS EM ÁGUAS SUBTERRÂNEAS DO MUNICÍPIO DE ROSÁRIO (MA) E SUAS POSSÍVEIS IMPLICAÇÕES NA SAÚDE DA POPULAÇÃO - Santos, Raimundo Nonato dos (2011)
We conducted this study to evaluate the concentrations of sodium and other ions present in groundwater in the city of Rosario / Ma., Used for human consumption, and its implications on the health of the population. The methodology used was exploratory literature search, following a line of approach to quantitative analysis of data obtained from the analysis of water from wells located in urban and rural zone, application questionnaires with open and closed questions in the village of São Simão on sociodemographic characteristics and health of the population, a survey of cases of hypertension of regional Baixo Munim and specifically the city of Rosario, with emphasis on the village of São Simão. Were studied physico-chemical characteristics of water, particularly sodium levels existing in the water for public supply and maintenance of the system as a whole. The study concludes that: In the Regional of Baixo Munim, Rosario is the municipality with the largest number of cases of hypertension with a predominance of the age group 55 to 59 years for females and 70 to 74 years for males; the supply system is deficient and lacks both the physical part of reformulations and the quality of water distributed; the well village of São Simão downtown, showed higher chloride concentrations equal to 423,20 mg / L, twice the allowable limit and sodium of 352,93mg / l, 152,93 above the limit, these values were compared with the limits established by the Ministry of Health Decree No. 518/04. It is recommended for action by local authorities, the current supply system of the municipality in order to improve the quality of distributed water and reduce the risk of harm to health.